Knee osteoarthritis. Efficacy of a new method of contrast-enhanced musculoskeletal ultrasonography in detection of synovitis in patients with knee osteoarthritis in comparison with magnetic resonance imaging. Issue 1 (14th May 2007) - Song, I H; Burmester, G R; Backhaus, M; Althoff, C E; Hermann, K G; Scheel, A K; Werner, C; Knetsch, T; Schoenharting, M
Abstract : Objective: To develop a new method of digital synovial vascularisation quantification by using contrast-enhanced musculoskeletal ultrasonography (MUS) in detecting synovitis in patients with knee osteoarthritis (OA) compared with healthy subjects and MRI. Methods: Evaluation of 41 patients with painful knee OA and 6 healthy subjects. The severity of knee pain was evaluated. All patients and all 6 healthy subjects underwent contrast medium-enhanced (CE)-MUS with SonoVue®, and 36 patients additionally underwent CE-MRI with Magnevist. Joint effusion, synovial thickening and pain were assessed and compared with B-mode and Power Doppler sonography (PDS) as well as contrast medium enhancement. Results: Pain evaluated by the visual analogue scale (VAS) hardly correlated with other markers of disease activity measured by ultrasound (US) in B-mode or MRI. US of the superior recess revealed an effusion or synovial thickening in 58%. PDS findings were positive in 63%, and CE-MUS in the superior knee recess was positive in 95%. MRI showed effusion in the superior recess in 61% and showed positive findings in 82% when using contrast medium. The kappa value was 0.48 between US and MRI with regard to the effusion in the superior recess, and 0.53 between PD signal in the superior recess and effusion in the superior recess by US. Using MRI as the reference standard, there was a sensitivity of 72% for assessing effusion in the superior recess and 81% for assessing effusion in the lateral recess. Conclusion: Assessment of disease activity (synovitis) in knee OA by VAS is not sufficient. US PDS was more sensitive than B-mode, and CE-MUS was more sensitive than PDS and CE-MRI in detecting synovitis in patients with painful knee OA. Also, CE-MRI was more sensitive in detecting inflammatory changes in the superior recess than without contrast medium. Using CE-MUS and performing time/intensity analysis has shown to be a good model for evaluation of an inflammatory process in the setting of knee OA in the superior recess.